(untitled) (Journal of Comparative Social Work, 2022)
The COVID-19 pandemic has rampaged through the daily life of individuals, increasing existing vulnerabilities and bringing about new ones. Social service workers act in close proximity and connection with these vulnerable groups, and measures taken to decrease the COVID-19 contamination rate — such as working from home, reducing social contacts and most of all lockdowns — negatively affect the core tasks of social service workers. Consequently, these professionals have had to find other ways to reach out to clients. This may potentially change the type of clients who have been reached and prioritized during the pandemic. Moreover, the profile of clients may have changed due to the pandemic. With this study, we address three research questions: (1) Which clients were prioritized by social service workers?, (2) Which clients were not able to be reached by social service workers?; and (3) Do social service workers expect a new vulnerable client base to emerge as a consequence of the COVID-19 pandemic? To help answer these questions, we used data from the Social Work COVID-19 Survey, obtained from 2,815 social service workers and collected in April and May 2020 during the first Belgian lockdown. The results indicate that urgent cases in need of essential, vital care were prioritized, with social service workers relying more on their gut instincts than on the customary procedures. Second, clients who could not be reached were those with limited access to modern communications, or with lower levels of digital skills. This often coincides with more vulnerable groups (such as people with mental health issues, financial issues, a small social network, the homeless and the elderly). Third, with regard to possible new clients, social service workers anticipate a ‘less standard’ and ‘more temporary’ client base, with more ‘middle-class families’ who have become vulnerable due to the economic consequences of the COVID-19 pandemic. Moreover, social service workers expect the pressure in the private life of individuals to increase, and have observed several mental health consequences of the COVID-19 pandemic.